1 - Mulheres e HIV/SIDA: Os Silêncios e as Vozes em Moçambique, Africa do Sul e Brasil – Políticas públicas e acesso aos serviços de saúde - Casimiro, Isabel Maria (Africa Development, 2021)
AIDS epidemic is growing in Mozambique, South Africa and Brazil, with different magnitudes, and different institutional responses to the epidemic and also the strategies of the social forces defending the human right to health. This epidemic takes opposite directions in relation to health policies adopted by the three countries, when considering the impacts of AIDS in vulnerable situations to poverty, gender inequalities and race. However, the expression of living with HIV/AIDS shows similarities, in an international context of economic globalization. Research involving Eduardo Mondlane University, Cape Town and the Federal de Pernambuco, in Brazil aims to deepen the meaning and content of these inequalities. This article seeks to understand prejudices and fears surrounding the life of HIV/AIDS sufferers. It discusses how health services are organized and how it affects the lives of women, but also men, marked by income, gender and color/ethnicity inequalities, who need state support of public policies – health, social care, housing, education and other, which are not always effective and available.